2017
DOI: 10.1007/s10067-017-3934-9
|View full text |Cite
|
Sign up to set email alerts
|

Ocular manifestations of IgG4-related disease in children. More common than anticipated? Review of the literature and case report

Abstract: IgG4-related disease (IgG4-RD) is an entity with various clinical manifestations. Histopathologically, it is characterized by lymphoplasmacytic infiltrates enriched in IgG4 (+) plasmacytes and usually fibrosis of the affected tissue. Most of the patients have also increased IgG4 serum levels and they respond to glucocorticosteroids. In children, due to its rare occurrence, IgG4-RD is ill defined. From the published studies, so far, it appears that ocular manifestations are very common in the paediatric populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 20 publications
0
14
0
1
Order By: Relevance
“…The first systematic review of head and neck IgG4-RD found that the orbit was the most frequently affected site [ 15 , 16 ]. Interestingly, an additional systematic review of pediatric IgG4-RD found that primary orbital disease was the most common manifestation in children [ 17 , 18 ]. Orbital IgG4-RD in adults usually involves the lacrimal gland; however, in children, the surrounding orbital soft tissues, musculature, and trigeminal nerve branches are more typically involved (as seen in our patient) [ 15 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first systematic review of head and neck IgG4-RD found that the orbit was the most frequently affected site [ 15 , 16 ]. Interestingly, an additional systematic review of pediatric IgG4-RD found that primary orbital disease was the most common manifestation in children [ 17 , 18 ]. Orbital IgG4-RD in adults usually involves the lacrimal gland; however, in children, the surrounding orbital soft tissues, musculature, and trigeminal nerve branches are more typically involved (as seen in our patient) [ 15 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, an additional systematic review of pediatric IgG4-RD found that primary orbital disease was the most common manifestation in children [ 17 , 18 ]. Orbital IgG4-RD in adults usually involves the lacrimal gland; however, in children, the surrounding orbital soft tissues, musculature, and trigeminal nerve branches are more typically involved (as seen in our patient) [ 15 , 18 ]. First-line IgG4-RD treatment is typically 2–4 weeks of steroids (usually prednisone) followed by a gradual taper [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 Breast carcinoma with sebaceous differentiation is also very rare with only 9 cases reported in the literature to our knowledge. 2,3 Sebaceous differentiation has been reported in association with invasive ductal carcinoma, adenoid cystic carcinoma and metaplastic carcinoma. 2 Hormone receptors and lymph node status vary between cases but none of the cases reported positive HER2 status.…”
mentioning
confidence: 99%
“…2,3 Sebaceous differentiation has been reported in association with invasive ductal carcinoma, adenoid cystic carcinoma and metaplastic carcinoma. 2 Hormone receptors and lymph node status vary between cases but none of the cases reported positive HER2 status. Here, we report a case of invasive carcinoma of no special type with focal sebaceous differentiation which is ER positive, PR positive, HER2 negative with two involved sentinel lymph nodes.…”
mentioning
confidence: 99%
See 1 more Smart Citation